THE POSITION OF THE UZBEK LANGUAGE: A COMPREHENSIVE ANALYSIS - Mamasolieva Nilufar Suyundikovna (Galaxy International Interdisciplinary Research Journal, 2024)
The position of the Uzbek language holds significant importance in our hands, as it reflects the cultural heritage and linguistic diversity of Uzbekistan. This scientific article provides a comprehensive analysis of the position of the Uzbek language in various domains, including education, media, government, and international communication. It examines the historical context, language policies, and challenges faced in promoting and preserving the Uzbek language. The article also highlights the efforts made to strengthen the position of the Uzbek language and suggests strategies for its further development and integration in the global linguistic landscape.